Population pharmacometric analyses of eribulin in patients with locally advanced or metastatic breast cancer previously treated with anthracyclines and taxanes. (10th June 2014) - Majid, Oneeb; Gupta, Anubha; Reyderman, Larisa; Olivo, Martin; Hussein, Ziad
Abstract Pharmacometric investigation of eribulin was undertaken in patients with metastatic breast cancer (MBC) and other advanced solid tumors. A population pharmacokinetic (PK) model used data combined from seven phase 1 studies (advanced solid tumors; n = 129), and one phase 2 (MBC; n = 211), and one phase 3 study (MBC; n = 173). Phase 3 data were also used in a PK/pharmacodynamic (PD) model of efficacy and tumor response (sum of longest diameters of target lesions). All analyses used NONMEM 7.2. Eribulin PK, described by a dose‐independent, three‐compartment model with allometric relationship for body weight, was similar for all tumor types. Inter‐individual variability (IIV) was 52% for both exposure and clearance. Liver function markers (albumin, alkaline phosphatase, bilirubin) significantly influenced eribulin PK (7.3% of IIV in clearance). Tumor shrinkage correlated with eribulin exposure; a 36% decrease in tumor size from baseline was modeled at week 36. No patient/disease factors significantly predicted eribulin's effect on tumor size. At week 6, a decrease in tumor size was associated with longer survival than an increase (P = .0055), suggesting survival may relate indirectly to eribulin exposure. These pharmacometric analyses provide a detailed overview of eribulin exposure–efficacy relationships to inform physicians treating patients with MBC.